د ا رسة مقارنة بين خوارزميات التشفير التقليدية وخوارزميات ما بعد التشفير الكمي في ظل التهديدات الكمية )إج ا رء مقارنة تحليلية بين خوارزمية التشفير المتماثل المتقدمة AES وخوارزمية ما بعد التشفير الكمي CRYSTALS-Kyber (Comprehensive Journal of Science, 2025)
This study aims to provide a comprehensive theoretical review of classical and quantum cryptography concepts, highlighting the fundamental differences between traditional algorithms and post-quantum algorithms. An analytical comparison is conducted between the Advanced Encryption Standard (AES), a symmetric encryption algorithm, and the post-quantum encryption algorithm CRYSTALS-Kyber, focusing on security levels and performance efficiency. The study also addresses key challenges associated with transitioning to quantum-resistant cryptographic environments, offering an analysis of the strengths and weaknesses of each algorithm under review. This is particularly relevant in light of the rapid advancements in quantum computing technologies and their implications for the future of information security. In addition to assessing the readiness of these algorithms to address future security challenges, the study provides a detailed comparison of the protection levels offered by each of the two algorithms.